2014
DOI: 10.1002/2014ja020297
|View full text |Cite
|
Sign up to set email alerts
|

Heliosheath magnetic field and plasma observed by Voyager 2 during 2011

Abstract: We discuss magnetic field and plasma observations from Voyager 2 (V2) during 2011, when V2 was beginning to see the effects of increasing solar activity following the solar minimum in 2009. The magnetic field strength (B) profile showed large amplitude fluctuations that can be resolved into a linear increase of B with time and a sinusoidal variation of the period of 86.2 ± 0.8 days. Voyager 2 was in a unipolar region in which the magnetic polarity was directed away from the Sun along the Parker spiral 96% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The sunspot number began increasing significantly in 2010 and 2011. Burlaga et al (2014) found that the minimum latitudinal extent of the HCS from the solar equatorial plane occurred near solar minimum, at which time V2 was in a unipolar region sampling magnetic fields from the southern coronal hole during 2011, consistent with the propagation time of the solar wind from 1 to ≈90 au being approximately 1 year. The smooth sunspot number reached alocal maximum of 66.9 in 2012 February and a maximum in 2014 (making it the smallest sunspot cycle since cycle 14 in 1906) and it decreased during 2015 and 2016.…”
Section: Overviewmentioning
confidence: 64%
See 1 more Smart Citation
“…The sunspot number began increasing significantly in 2010 and 2011. Burlaga et al (2014) found that the minimum latitudinal extent of the HCS from the solar equatorial plane occurred near solar minimum, at which time V2 was in a unipolar region sampling magnetic fields from the southern coronal hole during 2011, consistent with the propagation time of the solar wind from 1 to ≈90 au being approximately 1 year. The smooth sunspot number reached alocal maximum of 66.9 in 2012 February and a maximum in 2014 (making it the smallest sunspot cycle since cycle 14 in 1906) and it decreased during 2015 and 2016.…”
Section: Overviewmentioning
confidence: 64%
“…Each of the enhancements in CRI B in Figure 11(a) probably corresponds to an MIR (Burlaga et al 1993(Burlaga et al , 2014 produced by the interaction of two or more ejecta or corotating interaction regions. None of the MIRs had a strong and sustained (lasting two or more solar rotations) enhancement in B, indicating that V2 observed no GMIRs during 2013 and 2014, in contrast to the GMIR observed by V2 during 2012 .…”
Section: Cr-b Relationshipmentioning
confidence: 93%
“…Solar activity during solar cycle 23 decreased to minimum value in August 2009, when the monthly mean sunspot number was zero. Burlaga et al (2014) found that the minimum latitudinal extent of the heliospheric current sheet (HCS) from the solar equatorial plane occurred near solar minimum, leaving V2 in a unipolar region sampling magnetic fields from the southern coronal hole during 2011, consistent with the propagation time of the solar wind from 1 to ≈90 au being approximately 1 year.…”
Section: Introductionmentioning
confidence: 85%
“…Solar activity and B at 1 au increased after mid-2009, so one expects to observe increasingly strong magnetic fields at V2 after a propagation time from the Sun of ≈1 year. Relatively strong magnetic fields were observed at V2 during 2011 (Burlaga et al 2014) and during 2012 (as shown in Figure 2(a)).…”
Section: Magnetic Field Observationsmentioning
confidence: 92%
See 1 more Smart Citation